Pelvic dysfunction in women as a consequence of anatomical and functional changes of the pelvic floor during pregnancy and a reflection of adaptation to childbirth: A review - Aleksandr A. Bezmenko; Anna S. Staroverova (Гинекология)
The review describes hormonal and biochemical changes during pregnancy that have a multifaceted effect on the structure and function of the pelvic floor and are an adaptive mechanism for stretching during the baby's passage through the birth canal. It has been shown that the onset of pelvic dysfunctions during pregnancy is a reflection of the stages of connective tissue remodeling. Pregnancy, as an additional factor affecting pelvic floor function, may be a trigger for pelvic organ prolapse. In pregnant women with insufficient adaptation of the pelvic floor, injuries during childbirth are more common, and disorders of remodeling the connective tissue components lead to pelvic organ prolapse and subsequent pelvic dysfunction. The mechanism of impaired pelvic floor connective tissue remodeling during pregnancy remains unclear and requires further research.